PRESUPPOSITION AND COMMON GROUND OF THE CHARACTERS IN THE MOVIE GIFTED (2017) - Fauza Zuryatina; Sari Rejeki; Maulana Taufik (Journal Albion : Journal of English Literature, Language, and Culture, 2020)
This study is aimed to identify the kinds of presupposition and the triggers used by the characters in the movie Gifted. It is also aimed to interpret the implicit meaning in them and to describe the common ground between the speakers and the listeners. This study is a qualitative research using descriptive analysis method. The data are collected by using uninvolved observation and note-taking technique. The analysis result shows that there are 54 data of presupposition usages and common ground. According to the analysis, presupposition and common ground commonly appear more in daily communication caused by the triggers of implicit assumption, the close relationship between the speakers and the listeners, and the community they are attending.Keywords: common ground; presupposition;character.